A DIACHRONIC–PRAGMATIC MODEL FOR THE ANALYSIS OF AL-AḌDĀD IN CLASSICAL AND MODERN LINGUISTIC SCHOLARSHIP - Sirojiddin SOTVOLDIEV (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
The phenomenon of al-Aḍdād (الأضداد), commonly described as the coexistence of two opposite meanings within a single lexical form, occupies a unique position in Arabic linguistic thought. Since the earliest stages of Arabic lexicography, scholars have debated whether such lexical items represent a genuine linguistic phenomenon or merely reflect dialectal variation, semantic change, and contextual reinterpretation. While classical scholars compiled extensive corpora of al-Aḍdād and regarded them as an inherent feature of Arabic, other scholars questioned their legitimacy, arguing that a linguistic sign cannot simultaneously denote contradictory meanings without undermining communicative clarity. Contemporary studies have revived this debate through the frameworks of semantic change, enantiosemy, polysemy, and pragmatic interpretation. This study aims to integrate diachronic and pragmatic perspectives into a unified analytical model for examining Arabic enantiosemy.